Selected Poems and Letters of Sylvia Plath’s: Constructions of Depersonalization - Atif Ghalib; Siti Noor Fazelah Mohd Noor (Development in Language Studies, 2024)
This article examined Sylvia Plath’s hysterical symptoms through the lens of depersonalization. This article investigated Plath’s “Daddy”, “Mirror” and some selected letters that reflect her hysteria. The study adopted two methods which are the American Psychiatric Association approach in which depersonalization is classified as a hysteric psychoform of consciousness and awareness and Attitude analysis from the Systemic Functional Linguistics. The texts were analyzed using thematic analysis to obtain the results. As discovered in the study, many poems and letters of Plath illustrated how she was treated as an object or a commodity under male domination during her time. One of the significant depersonalization disorders is associated with detachment from oneself, highlighted in Plath’s selected literary works. In sum, Plath represented depersonalisation as a memorable response to suffering situations such as emotional abuse, stress, and imprisonment in her life.